Evaluating the Validity of the Clavien–Dindo Classification in Colectomy Studies: A 90-Day Cost of Care Analysis. Issue 11 (15th October 2021) - Widmar, Maria; Keskin, Metin; Strombom, Paul D.; Gennarelli, Renee L.; Szeglin, Bryan C.; Smith, J. Joshua; Nash, Garrett M.; Weiser, Martin R.; Paty, Philip B.; Russell, David; Garcia-Aguilar, Julio
Abstract : Supplemental Digital Content is available in the text. Abstract : BACKGROUND: The Clavien–Dindo classification is widely used to report postoperative morbidity but may underestimate the severity of colectomy complications. OBJECTIVE: The purpose of this study was to assess how well the Clavien–Dindo classification represents the severity of all grades of complications after colectomy using cost of care modeling. DESIGN: This was a retrospective cohort study. SETTINGS: The study was conducted at a comprehensive cancer center. PATIENTS: Consecutive patients (N = 1807) undergoing elective colon or rectal resections without a stoma performed at Memorial Sloan Kettering Cancer Center between 2009 and 2014 who were followed up for ≥90 days, were not transferred to other hospitals, and did not receive intraperitoneal chemotherapy were included in the study. MAIN OUTCOME MEASURES: Complication severity was measured by the highest-grade complication per patient and attributable outpatient and inpatient costs. Associations were evaluated between patient complication grade and cost during 3 time periods: the 90 days after surgery, index admission, and postdischarge (<90 d). RESULTS: Of the 1807 patients (median age = 62 y), 779 (43%) had a complication; 80% of these patients had only grade 1 or 2 complications. Increasing patient complication grade correlated with 90-day cost, driven by inpatient cost differences ( p < 0.001). For grade 1 and 2 patients, most costs were incurred after discharge and were the same between these grade categories. Among patients with a single complication (52%), there was no difference in index hospitalization, postdischarge, or total 90-day costs between grade 1 and 2 categories. LIMITATIONS: The study was limited by its retrospective design and generalizability. CONCLUSIONS: The Clavien–Dindo classification correlates well with 90-day costs, driven largely by inpatient resource use. Clavien–Dindo does not discriminate well among patients with low-grade complications in terms of their substantial postdischarge costs. These patients represent 80% of patients with a complication after colectomy. Examining the long-term burden associated with complications can help refine the Clavien–Dindo classification for use in colectomy studies. See Video Abstract at http://links.lww.com/DCR/B521 . EVALUACIÓN DE LA VALIDEZ DE LA CLASIFICACIÓN DE CLAVIEN-DINDO EN ESTUDIOS DE COLECTOMÍA: ANÁLISIS DEL COSTO DE LA ATENCIÓN EN 90 DÍAS: ANTECEDENTES: La clasificación de Clavien-Dindo es utilizada ampliamante para conocer la morbilidad posoperatoria, pero puede subestimar la gravedad de las complicaciones de la colectomía. OBJETIVO: Evaluar que tan bien representa la clasificación de Clavien-Dindo la gravedad de todos los grados de complicaciones después de la colectomía utilizando un modelo de costo de la atención. DISEÑO: Estudio de cohorte retrospectivo. ENTORNO CLÍNICO: Centro oncológico integral. PACIENTES: Pacientes consecutivos ( n = 1807) sometidos a resecciones electivas de colon o recto sin estoma realizadas en el Memorial Sloan Kettering Cancer Center entre 2009 y 2014 que fueron seguidos durante ≥ 90 días, no fueron transferidos a otros hospitales y no recibieron quimioterapia intraperitoneal. PRINCIPALES MEDIDAS DE VALORACION: Gravedad de la complicación medida por la complicación de mayor grado por paciente y los costos atribuibles para pacientes ambulatorios y hospitalizados. Se evaluó la asociación entre el grado de complicación del paciente y el costo durante 3 períodos de tiempo: posterior a la cirugía (hasta 90 días), a su ingreso y posterior al egreso (hasta 90 días). RESULTADOS: De los 1807 pacientes (mediana de edad de 62 años), 779 (43%) tuvieron una complicación; El 80% de estos pacientes tuvieron solo complicaciones de grado 1 o 2. El aumento del grado de complicación del paciente se correlacionó con el costo a 90 días, impulsado por las diferencias en el costo de los pacientes hospitalizados ( p <0, 001). Para los pacientes de grado 1 y 2, la mayoría de los costos se incurrieron después del alta y fueron los mismos entre ambas categorías. Entre los pacientes con una sola complicación (52%), no hubo diferencia en el índice de hospitalización, posterior al alta o en el costo total de 90 días entre las categorías de grado 1 y 2. LIMITACIONES: Diseño retrospectivo, generalizabilidad. CONCLUSIONES: La clasificación de Clavien-Dindo se correlaciona bien con los costos a 90 días, impulsados en gran parte por la utilización de recursos de pacientes hospitalizados. Clavien-Dindo no discrimina entre los pacientes con complicaciones de bajo grado en términos de sus costos sustanciales posterior al alta. Estos pacientes representan el 80% de los pacientes aquellos con una complicación tras la colectomía. Examinar la carga a largo plazo asociada a las complicaciones puede ayudar a mejorar la clasificación de Clavien-Dindo para su uso en estudios de colectomía. Consulte Video Resumen en http://links.lww.com/DCR/B521 .